2016
DOI: 10.5935/1806-6690.20160065
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient use efficiency in interspecific hybrids of eucalypt

Abstract: -The aim of this work was to evaluate nutrient use efficiency in interspecific hybrids of eucalypt, as an aid in the development of forest breeding programs for areas with limited nutrients. To do this, five clones were evaluated at 2.25 years of age from hybrids resulting from crosses of Eucalyptus grandis x E. urophylla (C1, C2, C3, C4 and C5). The experimental design was of randomised blocks, with single-tree plots and 35 replications. For the study, four trees of average performance were cut down (replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 11 publications
2
6
0
8
Order By: Relevance
“…On the one hand, comparing the data of this study for clones and seedlings, the NAI, or cost per unit of wood yield in terms of two of the most limiting nutrients in the area (P and Ca) may therefore be reduced considerably (45 and 35% less, respectively) by using genetically improved material. The selection of genotypes with more efficiency in the use of nutrients has been applied for hybrid eucalypts in Brazil (Rosim et al 2016). In a study carried out in Congo, Safou-Matondo et al (2005) demonstrated the superiority of several clones of Eucalyptus urophylla regarding P (+ 72%) and Ca (+ 43 to + 59%) assimilation index.…”
Section: Conventional Pulp Plantationsmentioning
confidence: 99%
“…On the one hand, comparing the data of this study for clones and seedlings, the NAI, or cost per unit of wood yield in terms of two of the most limiting nutrients in the area (P and Ca) may therefore be reduced considerably (45 and 35% less, respectively) by using genetically improved material. The selection of genotypes with more efficiency in the use of nutrients has been applied for hybrid eucalypts in Brazil (Rosim et al 2016). In a study carried out in Congo, Safou-Matondo et al (2005) demonstrated the superiority of several clones of Eucalyptus urophylla regarding P (+ 72%) and Ca (+ 43 to + 59%) assimilation index.…”
Section: Conventional Pulp Plantationsmentioning
confidence: 99%
“…During restrictions in resource supply, these processes become critical. Higher AE and UE resulted in higher biomass yield (Rosim et al, 2016), allowing maintenance of productivity, mainly on nutrient-poor soils. Consequently, genotypes with greater capacity of nutrient absorption and/or use are more desirable (Godoy and Rosado, 2011), because, in addition to a better exploitation of the fertilized nutrients, smaller amounts of nutrients are required for growth (increased efficiency).…”
Section: Responses In Growth Traits As Indicators Of Drought Tolerancmentioning
confidence: 99%
“…Na literatura, diversos são os estudos que avaliam a EUN para selecionar espécies ou clones na área florestal (DICK et al, 2017;SILVA, 2017;ROSIM et al, 2016;MEDEIROS et al, 2016;GUIMARÃES et al, 2015;FARIA et al, 2008), especialmente para o Eucalyptus urograndis, clone H13 em consórcio de ILPF (CARVALHO, 2017), compreendendo especialmente, os compartimentos da biomassa exportados na colheita (tronco e casca).…”
Section: Introductionunclassified